EP-148 Acute appendicitis complicated by COVID-19: an unexpected postsurgical sequela, Case Presentation. (9th August 2022) - Ahmed, Salma; Zaver, Vasudev; Shafi, Adil; Al-Hamid, Zaid
Abstract: Background: This is a case in which we explore the presentation and management of a 62-year-old gentleman, who attended a UK based surgical unit with appendicitis and a positive COVID-19 on admission. Following an urgent appendicectomy, he suffered a morbid and protracted postoperative period, complicated by an upper gastrointestinal bleed and prolonged ileus. The virus has been recognised to increase the risk of micro-thromboembolic events and gastrointestinal complications. We discuss the possibility of COVID-19 causing the patient's presentation and his post-surgical recovery. We aim to demonstrate our experience of the relationship between acute appendicitis and the morbidity associated with COVID-19. Discussion: The case demonstrates a unique sequela following an otherwise routine emergency appendicectomy. In concurrence with a radiologically and microbiologically evident COVID-19 infection, it raises the question of whether the appendicitis was caused or at least complicated by the virus. This hypothesis is supported by a similar discovery in a case series carried out in Wuhan, in which a paediatric patient acutely presented with a perforated appendix in parallel with a SARSCoV-2 infection, which required urgent surgery. Contrastingly, a case which involved a COVID-19 positive adult male with a non-perforated and non-suppurative appendix demonstrated no complications post-operatively. Conclusion: It is possible to postulate that the severe presentation outlined in our case could also have been caused by a delayed COVID-19 presentation. However, there is currently no formal research to support this and the approach has not been exemplified in a complex case such as ours.